2020
DOI: 10.1111/cei.13472
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormal processing of IL-1β in NLRP7-mutated monocytes in hydatidiform mole patients

Abstract: Summary NOD‐like receptor pyrin 7 (NLRP7) has been identified as the major gene responsible for the recurrent hydatidiform mole (RHM). The immunological role of NLRP7 mutation in HM patients has not been conclusively demonstrated. Hence, we aim to demonstrate this role in our study. We followed 12 new patients with NLRP7 non‐synonymous variations (NSVs) from date to date. Peripheral blood mononuclear cells (PBMCs) were collected separately from patients with and without NLRP7 mutation. Supernatant interleukin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Investigating the inflammatory response of ex‐vivo stimulated peripheral blood mononuclear cells from two patients with biallelic NLRP7 variants (p.Gly118Aspfs and p.Arg693Trp, both in a homozygous state) demonstrated that these cells, as opposed to those of patients with NLRP3 variants, have decreased IL‐1B and TNF secretion in the extracellular milieu. Another recent study by Zhang et al (2020), reproduced these results using the same assay on cells from six other patients with biallelic NLRP7 variants (p.Arg432*, p.Arg693Gln, and p.Arg721Trp in homozygous state and the following in compound heterozygous state, p.Asp722Gly with p.Trp920*, p.Asp722Gly with p.Leu825*, and p.Arg432* with p.Ala719Val). This study confirmed the requirement of normal NLRP7 for normal IL‐1B and TNF production.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Investigating the inflammatory response of ex‐vivo stimulated peripheral blood mononuclear cells from two patients with biallelic NLRP7 variants (p.Gly118Aspfs and p.Arg693Trp, both in a homozygous state) demonstrated that these cells, as opposed to those of patients with NLRP3 variants, have decreased IL‐1B and TNF secretion in the extracellular milieu. Another recent study by Zhang et al (2020), reproduced these results using the same assay on cells from six other patients with biallelic NLRP7 variants (p.Arg432*, p.Arg693Gln, and p.Arg721Trp in homozygous state and the following in compound heterozygous state, p.Asp722Gly with p.Trp920*, p.Asp722Gly with p.Leu825*, and p.Arg432* with p.Ala719Val). This study confirmed the requirement of normal NLRP7 for normal IL‐1B and TNF production.…”
Section: Resultsmentioning
confidence: 63%
“…This suggests its African ancestral origin and later introduction to the Indo‐Pakistani population via migration. The p.Arg721Trp and p.Leu825* variants were present mainly in Indo‐Pakistani (Kou et al, 2008; Murdoch et al, 2006; Sanchez‐Delgado et al, 2015; C. M. Wang et al, 2009) and Chinese (Qian et al, 2011; Zhang et al, 2020) patients and to a lesser extent in other populations. In Egyptians, variant p.Glu710Aspfs slightly dominated the others (32% of the alleles) and again this variant has not been reported in other populations (Kou et al, 2008; Mahadevan et al, 2013; Panichkul et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Abi Nahed et al recently demonstrated that the activation of the NLRP7 inflammasome in a trophoblastic cell line induced the secretion of IL1β but not IL18 [ 150 ]. Numerous studies have described the involvement of the NLRP7 inflammasome in some obstetrical complications, such as the recurrent hydatidiform mole (a disease characterized by an excessive trophoblastic proliferation without embryonic development), especially those related to mutations of NLRP7 [ 151 , 152 , 153 , 154 , 155 ]. In addition, the NLRP7 inflammasome is highly expressed by placental trophoblast cells and is deregulated in fetal growth restrictions, a disorder importantly related to abnormal placental development [ 150 ].…”
Section: Inflammasomesmentioning
confidence: 99%
“…In the article by Zhang et al, 1 the funder Key Research and Development Program of Zhejiang Province (2020C03116) were missed out and should have been added to the acknowledgement section.…”
mentioning
confidence: 99%